Real power loss reduction by Toxotes kimberleyensis, Opposition based Chaotic Septentrion Red Snapper and Charidotella based optimization algorithms - Kanagasabai, Lenin (International journal of system assurance engineering and management, 2023)
In this paper Toxotes kimberleyensis optimization (TKO) algorithm, Opposition based Chaotic Septentrion Red Snapper optimization (OCNRS) algorithm and Charidotella based optimization (CO) algorithm are applied for solving the power loss lessening problem. The procedure is enthused by the shelling and hurdling activities of Toxotes kimberleyensis while grasping the prey. TKO approach possesses “3” governing variables to fix the population scale, the exchange angle amongst the exploration and exploitation segments, and the attraction degree amongst the Toxotes kimberleyensis and target. OCNRS algorithm has been designed based on the actions and physiognomies of Septentrion red snapper. Freshly produced Septentrion Red snapper banquet out over enormous expanses of uncluttered benthic environment. Then in this paper CO algorithm is used for solving the power loss lessening problem. CO algorithm impressionists Charidotella action of altering colours to fascinate opposite sex for breeding and its defensive approach that expenditures a compassionate of anal cleft to dissuade slayers. The regime of Charidotella has enthused to come up with a fresh optimization technique that scientifically replicas their colour swapping performance for fascinating the opposite sex to breeding and their endurance method for shielding themselves from slayers. In this paper each Charidotella signifies a solution. Proposed TKO algorithm, OCNRS algorithm and CO algorithm are corroborated in IEEE 30 bus system and IEEE 14, 30, 57, 118, 300 bus test systems without considering the voltage constancy index. True power loss lessening, voltage divergence curtailing, and voltage constancy index augmentation has been attained.